2005
DOI: 10.1128/mcb.25.24.10815-10821.2005
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Activation-Induced Cytosine Deaminase Is Strongly Influenced by the Sequence and Structure of the Targeted DNA

Abstract: Activation-induced deaminase (AID) initiates immunoglobulin somatic hypermutation (SHM). Since in vitroAID was shown to deaminate cytosines on single-stranded DNA or the nontranscribed strand, it remained a puzzle how in vivo AID targets both DNA strands equally. Here we investigate the roles of transcription and DNA sequence in cytosine deamination. Strikingly different results are found with different substrates. Depending on the target sequence, the transcribed DNA strand is targeted as well as or better th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 26 publications
6
55
3
Order By: Relevance
“…It is thus very unlikely that AID targets these regions. This is strikingly different from the result of the cell-free study that showed that AID could access cytidines immediately downstream of the promoter in naked DNAs (44). Therefore, the interesting questions that remain are whether in vivo AID may be associated with transcription complexes only in the ϳϩ100 nt to ϳϩ2 kb region of Ig genes, whether it can only access this region even without association with the transcription complex, or whether it is present in complexes with DNA in the 5Ј and 3Ј regions but cannot act.…”
Section: Discussioncontrasting
confidence: 52%
“…It is thus very unlikely that AID targets these regions. This is strikingly different from the result of the cell-free study that showed that AID could access cytidines immediately downstream of the promoter in naked DNAs (44). Therefore, the interesting questions that remain are whether in vivo AID may be associated with transcription complexes only in the ϳϩ100 nt to ϳϩ2 kb region of Ig genes, whether it can only access this region even without association with the transcription complex, or whether it is present in complexes with DNA in the 5Ј and 3Ј regions but cannot act.…”
Section: Discussioncontrasting
confidence: 52%
“…An alternative, but not mutually exclusive, model for generating AID‐accessible ssDNA is based on the formation of denaturation bubbles generated by transcription‐associated negative supercoiling (Shen & Storb, 2004; Shen et al , 2005; Parsa et al , 2012). In regions of very active transcription, topoisomerase‐mediated resolution of the negative supercoiling generated in the wake of RNAPII does not appear to be able to keep pace resulting in overall negative supercoiling upstream of RNAPII (Kouzine et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In regions of very active transcription, topoisomerase‐mediated resolution of the negative supercoiling generated in the wake of RNAPII does not appear to be able to keep pace resulting in overall negative supercoiling upstream of RNAPII (Kouzine et al , 2008). Negative supercoiling creates localised denaturation bubbles (Jeon et al , 2010), which have been shown to provide an ideal substrate for AID on both strands of a plasmid, even in the absence of transcription (Shen & Storb, 2004; Shen et al , 2005). Transcription‐associated negative supercoiling has also been proposed to explain the short patches of AID and bisulphite‐accessible ssDNA observed in the Ig genes of hypermutating Ramos cells and stimulated murine primary B cells (Ronai et al , 2007; Parsa et al , 2012), which are similar to the patches of ssDNA we observe in the diversifying IGVL R of DT40 and, importantly, show are sensitive to the absence of H3.3.…”
Section: Discussionmentioning
confidence: 99%
“…However, available evidence suggests that AID catalyses several deaminations per molecule (17)(18)(19), which might give rise to several U/G mispairs in close proximity. We argued that in such a scenario, the picture might change.…”
Section: Partially-processed U/g Mispairs Can Serve As Initiation Sitmentioning
confidence: 99%